Nonresident Capital Flows and Volatility : Evidence from Malaysia's Local Currency Bond Market - Grigorian, David (IMF Working Papers; Working Paper ;, 2019)
Malaysia's local currency debt market is one of the most liquid public debt markets in the world. In recent years, the growing share of nonresident holders of debt has been a source of concern for policymakers as a reason behind exchange rate volatility. The paper provides an overview of the recent developments in the conventional debt market. It builds an empirical two-stage model to estimate the main drivers of debt capital flows to Malaysia. Finally, it uses a GARCH model to test the hypothesis that nonresident flows are behind the observed exchange rate volatility. The results suggest that the public debt market in Malaysia responds adequately to both pull and push factors and find no firm evidence that nonresident flows cause volatility in the onshore foreign exchange market.